Enterotoxigenic Escherichia coli heat-labile enterotoxin induces cell death and disrupts effector functions in porcine monocytes - Jinglin Ma; Hans Van der Weken; Leen Hermans; Matthias Dierick; Eric Cox; Bert Devriendt (Veterinary Research)
Abstract Enterotoxigenic Escherichia coli (ETEC) is a common cause of diarrhea in humans and animals, including pigs. Enterotoxins are important virulence factors for ETEC. Although much is known about the mechanism of enterotoxin-induced diarrhoea, less is known about its effects on innate immune cells such as monocytes. Monocytes can differentiate into macrophages and dendritic cells and play a pivotal role in bridging the innate and adaptive immune systems. Understanding the interaction between ETEC enterotoxins and monocytes can help in the development of more effective preventive and therapeutic strategies to combat this disease. In this study, we aimed to investigate the effects of heat labile enterotoxin (LT) and heat stable enterotoxin a (STa) produced by ETEC on porcine monocytes. Our results showed that STa did not affect the viability or effector functions of monocytes. LT, on the other hand, decreased the viability of monocytes. While LT did not alter the production of reactive oxygen species (ROS) by monocytes, it significantly reduced the production of ROS induced by phorbol 12-myristate 13-acetate (PMA). In addition, LT decreased the phagocytosis of E. coli by monocytes and enhanced the survival of intracellular ETEC. Furthermore, LT triggered the production of the cytokines IL-1β, IL-6 and TNF-α as well as the chemokines CCL-3 and CXCL-8. Together, our results show that, in contrast to STa, LT can cause monocyte death and disrupt monocyte immune effector functions, potentially acting as an immune evasion strategy to establish infection.